Karakteristik Proses Pembelajaran Kurikulum 2013 - Shafa, Shafa (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2014)
In PP No 32 tahun 2013, it was found that four of eight national educational standards has significantly changed. The four standards are: 1) the graduation compentency standard has been revised and renewed in Permendikbud No 54 Tahun 2013; 2) the content standard is renewed in Permendikbud No 64 Tahun 2013; 3) the process standard is renewed in Permendikbud No 65 Tahun 2013; and 4) evaluation standard is renewed in Permendikbud No 66 Tahun 2013. One of the four standards that is very interesting to discsuss is the process standard which is focusing on how the ideal model of a teacher plans, implements, and evaluates teaching and learning process. This process standard is one of the curriculum anatomies which covers a model, approach, strategy, method, and technique of teaching implemented by a teacher in administering the content of learning to achieve the goals of teaching has been made. This paper tries to explore the characteristics of ideal teaching targeted by the national curriculum 2013 which is focusing on the principles of learning, characteristics, planning, and the implementation of curriculum 2013.